Pergelaran Bantengan "Banteng Wareng" Madyopuro Malang: Telaah Antropologi Kesenian - radhia, hanifati alifa (Studi Budaya Nusantara, 2019)
This research represents the anthropology of art study of the Bantengan performance in Madyopuro, Malang. Bantengan is dance performance though kanuragan, as well as bull attraction played by two people as the head and tail. The main attractions Bantengan are their ancestral spirits of the players that enter the body. Bantengan performances involving the magical practice was popular in the era of globalization. Research on this Bantengan using the perspective of anthropology of art. In the anthropological study of art as described by Ahimsa-Putra (2000), known to approach the context of describing the phenomenon of art that highlight the socio-cultural side. Data was collected through observation (observation) and in-depth interviews (depth interview). Results showed that there are two dimensions of the Bantengan "Banteng Wareng" in Madyopuro. First, the social dimension, of Bantengan in Madyopuro live and grow at the initiative of local residents to turn on environmental activities andserves as entertainment. Second, the cultural dimension, Bantengan load tradition of Javanese culture is still preserved until now. The tradition appears in ritual practice before the performance Bantengan conducted in a beringin tree. In this beringin tree dwelling ancestors are believed to be the pedestal of the village Madyopuro loggers. Practices in the deployment of this Bantengan irrational, not unreasonable and contains magical side. Socio-cultural phenomenon in the performance Bantengan can be deconstructed in postmodern view. Thought dominant today is more we follow the ratio, the more advanced human civilization. Postmodernism actually appreciate, explore the wisdom of the past and to be heard all thought taboo, irrational, mystical and magical. As well as Bantengan by the breath of life by the "Banteng Wareng" indicate their cultural revitalization movement.